Islamic society between centrism and extremism: Anthropological reading in the Islamic texts - Al-Hassani, Ahmed Abdel-Rida Mohammed (Al-Adab Journal, 2019)
The study dealt with several topics, including: Muslim society extremism or moderation ?, and the Islamic text, standing on a set of texts and concepts that were manipulated by the hands of the situation and fraud, which constituted and continue to pose a threat to the structure of Muslim societies that have become and its value on love and human brotherhood Mushroom people on them. Such as the concepts of extremism and atonement founded by some of these texts aimed at presenting Muslims as advocates of evil and aggression and not accepting the other regardless of race and belonging. Therefore, the study tried to identify the trends of extremism and moderation and the texts of them, . The study adopted the analytical methodology based on the value anthropological approach, which deals with man according to his physical and spiritual existence, the two components which constitute his true and original identity..